Carbon respiration from subsurface peat accelerated by climate warming in the subarctic - Dorrepaal, Ellen; Toet, Sylvia; Logtestijn, Richard S.P. van; Swart, Elferra; Weg, Martine J. van de; Callaghan, Terry V; Aerts, Rien (Nature (London), 2009)
Among the largest uncertainties in current projections of future climate is the feedback between the terrestrial carbon cycle and climate. Northern peatlands contain one-third of the world's soil organic carbon, equivalent to more than half the amount of carbon in the atmosphere. Climate-warming-induced acceleration of carbon dioxide (CO2) emissions through enhanced respiration of thick peat deposits, centuries to millennia old, may form a strong positive carbon cycle–climate feedback. The long-term temperature sensitivity of carbon in peatlands, especially at depth, remains uncertain, however, because of the short duration or correlative nature of field studies and the disturbance associated with respiration measurements below the surface in situ or during laboratory incubations. Here we combine non-disturbing in situ measurements of CO2 respiration rates and isotopic (13C) composition of respired CO2 in two whole-ecosystem climate-manipulation experiments in a subarctic peatland. We show that approximately 1 °C warming accelerated total ecosystem respiration rates on average by 60% in spring and by 52% in summer and that this effect was sustained for at least eight years. While warming stimulated both short-term (plant-related) and longer-term (peat soil-related) carbon respiration processes, we find that at least 69% of the increase in respiration rate originated from carbon in peat towards the bottom (25–50 cm) of the active layer above the permafrost. Climate warming therefore accelerates respiration of the extensive, subsurface carbon reservoirs in peatlands to a much larger extent than was previously thought. Assuming that our data from a single site are indicative of the direct response to warming of northern peatland soils on a global scale, we estimate that climate warming of about 1 °C over the next few decades could induce a global increase in heterotrophic respiration of 38–100 megatonnes of C per year. Our findings suggest a large, long-lasting, positive feedback of carbon stored in northern peatlands to the global climate system.